An aromatic imidazoline derived from chloroquinoline triggers cell cycle arrest and inhibits with high selectivity the Trypanosoma cruzi mammalian host-cells infection. - Roberto I Cuevas-Hernández; Richard M B M Girard; Luka Krstulović; Miroslav Bajić; Ariel Mariano Silber (Public Library of Science (PLoS), 2021)
Trypanosoma cruzi is a hemoflagellated parasite causing Chagas disease, which affects 6-8 million people in the Americas. More than one hundred years after the description of this disease, the available drugs for treating the T. cruzi infection remain largely unsatisfactory. Chloroquinoline and arylamidine moieties are separately found in various compounds reported for their anti-trypanosoma activities. In this work we evaluate the anti-T. cruzi activity of a collection of 26 "chimeric" molecules combining choroquinoline and amidine structures. In a first screening using epimastigote forms of the parasite as a proxy for the clinically relevant stages, we selected the compound 7-chloro-4-[4-(4,5-dihydro-1H-imidazol-2-yl)phenoxy]quinoline (named here as A6) that performed better as an anti-T. cruzi compound (IC50 of 2.2 ± 0.3 μM) and showed a low toxicity for the mammalian cell CHO-K1 (CC50 of 137.9 ± 17.3 μM). We initially investigated the mechanism of death associated to the selected compound. The A6 did not trigger phosphatidylserine exposure or plasma membrane permeabilization. Further investigation led us to observe that under short-term incubations (until 6 hours), no alterations of mitochondrial function were observed. However, at longer incubation times (4 days), A6 was able to decrease the intracellular Ca2+, to diminish the intracellular ATP levels, and to collapse mitochondrial inner membrane potential. After analysing the cell cycle, we found as well that A6 produced an arrest in the S phase that impairs the parasite proliferation. Finally, A6 was effective against the infective forms of the parasite during the infection of the mammalian host cells at a nanomolar concentration (IC50(tryps) = 26.7 ± 3.7 nM), exhibiting a selectivity index (SI) of 5,170. Our data suggest that A6 is a promising hit against T. cruzi.